A numerical study to investigate the effects of tumour position on the treatment of bladder cancer in mice using gold nanorods assisted photothermal ablation. (November 2021) - Cheong, Jason KK.; Popov, Viktor; Alchera, Elisa; Locatelli, Irene; Alfano, Massimo; Menichetti, Luca; Armanetti, Paolo; Maturi, Mirko; Franchini, Mauro Comes; Ooi, Ean H.; Chiew, Yeong S.
Abstract: Gold nanorods assisted photothermal therapy (GNR-PTT) is a new cancer treatment technique that has shown promising potential for bladder cancer treatment. The position of the bladder cancer at different locations along the bladder wall lining can potentially affect the treatment efficacy since laser is irradiated externally from the skin surface. The present study investigates the efficacy of GNR-PTT in the treatment of bladder cancer in mice for tumours growing at three different locations on the bladder, i.e., Case 1: closest to skin surface, Case 2: at the bottom half of the bladder, and Case 3: at the side of the bladder. Investigations were carried out numerically using an experimentally validated framework for optical-thermal simulations. An in-silico approach was adopted due to the flexibility in placing the tumour at a desired location along the bladder lining. Results indicate that for the treatment parameters considered (laser power 0.3 W, GNR volume fraction 0.01% v/v), only Case 1 can be used for an effective GNR-PTT. No damage to the tumour was observed in Cases 2 and 3. Analysis of the thermo-physiological responses showed that the effectiveness of GNR-PTT in treating bladder cancer depends not only on the depth of the tumour from the skin surface, but also on the type of tissue that the laser must pass through before reaching the tumour. In addition, the results are reliant on GNRs with a diameter of 10 nm and an aspect ratio of 3.8 - tuned to exhibit peak absorption for the chosen laser wavelength. Results from the present study can be used to highlight the potential for using GNR-PTT for treatment of human bladder cancer. It appears that Cases 2 and 3 suggest that GNR-PTT, where the laser passes through the skin to reach the bladder, may be unfeasible in humans. While this study shows the feasibility of using GNRs for photothermal ablation of bladder cancer, it also identifies the current limitations needed to be overcome for an effective clinical application in the bladder cancer patients. Graphical abstract: Image 1 Highlights: 3D models of mouse bladder was constructed from images obtained from MRI. Tumour position can significantly affect treatment efficacy of GNR-PTT. Tumour below the skin surface can be ablated with a 0.3 W laser and 0.01% v/v GNR. Tumours located elsewhere cannot be ablated with the same laser and GNR setting.